Configuration and Visualization of Spanning Tree Protocol (STP) for VLAN-Based Using Packet Tracer - Misinem, .; Alfin, Triarso (INTI International University, 2023)
In this era of globalization, scientific and technological progress is increasing, and so is the company we work with, the PT. Telkom Rivai. The company has discovered that computer networks are essential especially because they use and manage the kind of Local Area Network (LAN). Most LAN problems are the absence of a backup link and frequent looping in switch devices that make the internet network inactive or stop functioning. This problem can be resolved by breaking the cycle using the Spanning Tree Protocol (STP) approach. Since there are no restrictions on access between divisions, it allows unauthorized or unidentified people to access data at the company. As a solution, we propose configuring and visualizing a Virtual Local Area Network (VLAN) with access privileges for each division. The last problem is data leakage for every division, which can be fixed by restricting access to certain regions of the division by activating Access List Control on the router.